Ways to solve the agency problem in corporate governance: the role of accounting - V.Yu. Tsaruk (Економіка, управління та адміністрування)
The expedience of conducting scientific researches in the direction of solving the agency problem in corporate management is grounded. The historical aspects of the formation of theoretical foundations of the phenomenon of information asymmetry are considered. The types of information asymmetry and their characteristics are analyzed. The influence of the effects of information asymmetry (unfavorable selection, moral hazard, retention) on the activity of corporate structures is considered. The ways of minimizing the negative impact of the agency problem on the activity of corporate structures are analyzed. Two groups of researchers’ approaches to solving the agency problem are identified in the context of the existence of a normative-positive dichotomy regarding the methodology of research. The necessity of taking into account the peculiarities of the internal and external environment of the corporate structure in the process of choosing methods to minimize the negative consequences of the agency problem is substantiated. The ways to improve accounting in the direction of minimizing the negative consequences of the agency problem are identified.